A 1-V feed-forward incremental modulator simulation based on gain-boost inverter for image sensors in 65-nm CMOS. Issue 12 (December 2015) - Xu, Jiangtao; Yin, Zhaoyang; Wang, Peng; Han, Liqiang; Lv, Tao
Abstract: This paper presents the analysis and implementation of a low-voltage and low-power incremental feed-forward modulator for CMOS image sensors, which is realized in the standard 65 nm CMOS technology. A feed-forward architecture and an integrator based on class-C inverter are employed in this modulator. Aiming to increase the signal-to-noise ratio (SNR) of the image sensors, the gain-boost technology is applied to this modulator. In order to optimize the integrator based on class-C inverter and satisfy a requirement for conversion speed of the modulator, the accurate mathematical expression of a charge transfer process of integrator based on class-C inverter is established. This incremental modulator operates in 1-V supply voltage, and achieves 80.4 dB SNR at 50 kS/s conversion rate with a 10 MHz sampling frequency. The offset error is 0.2 mV and the maximum integral nonlinearity (INL) is 0.97 LSB. In addition, its power consumption is 25-μW, which is particularly suitable for low-voltage high-resolution sensors applications.